Deconstructing the Association Between Financial-Psychological Factors and Financial Well-being: Evidence from the Nepalese Working Adults - Sharma, Dilli Raj; Dahal, Rewan Kumar; Lamichhane, Prabesh; Karki, Dipendra; Joshi, Surendra Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2026)
The study examines how financial knowledge (SFK), financial attitude (FA), and locus of control (LOC) affect the financial well-being (FWB) of Nepalese working adults, with financial behavior mediating the effects. A quantitative survey was conducted with 385 adult participants from the Kathmandu Valley. The researcher analyzed the data using SmartPLS 4.0 and IBM SPSS 22. Structural equation modeling reveals that SFK (β = 0.130, p < 0.05), FA (β = 0.341, p < 0.01), and LOC (β = 0.170, p < 0.01) significantly enhance FWB. Furthermore, financial behavior (β = 0.059, p > 0.05) does not significantly predict financial well-being and is not an effective mediator, indicating that psychological beliefs operate through routes other than behavioral ones in this context. The findings indicate that the theory of planned behavior works differently in developing countries, where structural obstacles and income instability reduce the relationship between actual well-being and intended behaviors. This evidence indicates that interventions to increase financial knowledge will require methods to build financial confidence and resiliency, in addition to standard behavioral approaches, but further studies are required to substantiate these suggestions.